2020
DOI: 10.3390/plants9020260
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity of the “Acquaviva Red Onion” (Allium cepa L.) Apulian Landrace

Abstract: Onion (Allium cepa L.) is the second most important vegetable crop worldwide and is widely appreciated for its health benefits. Despite its significant economic importance and its value as functional food, onion has been poorly investigated with respect to its genetic diversity. Herein, we surveyed the genetic variation in the “Acquaviva red onion” (ARO), a landrace with a century-old history of cultivation in a small town in the province of Bari (Apulia, Southern of Italy). A set of 11 microsatellite markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
7
2
Order By: Relevance
“…Allele number ranged from 2 to 4 which is lower to those found in our previous study of cpSSR of Allium paradoxum (Jayaswall et al2021,) but similar to Ziziphus cpSSR markers (Huang et al 2015). Compared to cpSSR, higher number of alleles were reported using genomic and EST-SSRs which could be due to higher sequence conservation in chloroplast genome (Ricciardi et al 2020;Baldwin et al 2012). In our previous work on Allium paradoxum cpSSRs, where PIC value ranged from 0.09 to 0.68 and heterozygosity from 0.104 to 0.733 (Jayaswall et al 2021) whereas in the present study, comparatively lower PIC (0.007 to 0.427) and heterozygosity (0.009 to 0.540)(Table 2) is observed that might be due to reduction in genetic diversity, during the process of domestication and selection of cultivated Alliums.…”
Section: Scoring and Data Analysiscontrasting
confidence: 66%
“…Allele number ranged from 2 to 4 which is lower to those found in our previous study of cpSSR of Allium paradoxum (Jayaswall et al2021,) but similar to Ziziphus cpSSR markers (Huang et al 2015). Compared to cpSSR, higher number of alleles were reported using genomic and EST-SSRs which could be due to higher sequence conservation in chloroplast genome (Ricciardi et al 2020;Baldwin et al 2012). In our previous work on Allium paradoxum cpSSRs, where PIC value ranged from 0.09 to 0.68 and heterozygosity from 0.104 to 0.733 (Jayaswall et al 2021) whereas in the present study, comparatively lower PIC (0.007 to 0.427) and heterozygosity (0.009 to 0.540)(Table 2) is observed that might be due to reduction in genetic diversity, during the process of domestication and selection of cultivated Alliums.…”
Section: Scoring and Data Analysiscontrasting
confidence: 66%
“…In India, onions are grown in a wide range of climatic conditions [ 2 ]. Onion is consumed both fresh as well as in the form of processed products, owing to its nutritional and medicinal properties [ 3 ]. Onion contains bioactive compounds (quercetin, rutin etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Onion (Allium cepa L.) is the second most broadly cultivated vegetable crop in the world for their economic importance, nutritional value, flavor, and medicinal properties [1]. In 2019, worldwide bulb onion production was approximately 100 million tons harvested from an area of approximately 5.2 million ha.…”
Section: Introductionmentioning
confidence: 99%